Exploring mediators of the Amaka Amasanyufu Multiple Family Group Intervention (2016–2022) on parenting stress reduction among caregivers of children with disruptive behavior disorders in Uganda - Rachel Brathwaite; Massy Mutumba; Fred M. Ssewamala; Ozge Sensoy Bahar; Torsten B. Neilands; Phionah Namatovu; Mary M. McKay; Kimberly Hoagwood (SSM - Mental Health)
Residing in poverty-impacted Ugandan communities and raising children with disruptive behavior disorders (DBDs) is associated with above heightened parenting stress. An evidence-based intervention designed to help parents tailor their parenting style to effectively manage children with DBDs was implemented in Uganda between 2017 and 2023. At the end of the intervention, caregivers displayed lower levels of parenting stress than controls, however the mechanisms by which stress reduction occurred is unknown. We investigated whether the intervention's effect on parenting stress was mediated by parenting practices, family cohesion, or mental health.Mediation was assessed using Mitchell and Maxwell's cross-lagged auto-regressive approach. Each mediation model regressed the outcome parenting stress score at each time point onto intervention group assignment (0 = Control; 1 = Multiple Family Group (MFG) intervention) and parenting stress score at the preceding time point. Each mediator was investigated one at a time and regressed onto intervention group assignment and the mediator score at the preceding time point. Parenting stress score was also regressed onto the preceding time point mediator score. The residuals for mediators and parenting stress were allowed to correlate at each time point. We included regression pathways from each covariate to the mediators and outcomes at subsequent waves and were included in the model as random variables.The findings show that the intervention had a significant direct effect on parenting stress at 16 weeks post intervention initiation and was partially mediated by parenting practices, caregiver mental health, and parenting stress at 8 weeks, but we found no evidence it was mediated by family cohesion, supporting two of our hypotheses.Equipping caregivers with parenting skills and strategies to improve mental health can go a long way in reducing overall parenting stress among caregivers with DBDs. Our findings could be leveraged to enhance stress reduction among caregivers of children with DBDs in the long-term.